2014
DOI: 10.7863/ultra.33.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Left Ventricular Function by 3‐Dimensional Speckle‐Tracking Echocardiography in Patients With Chronic Heart Failure

Abstract: This meta-analysis suggests that LV function in patients with CHF can be noninvasively and objectively measured by 3D speckle-tracking echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
1
18
0
3
Order By: Relevance
“…Furthermore, Tang and colleagues reported that plasma hs‐CRP levels progressively increase with worsening LV diastolic dysfunction. More advanced indices of LV diastolic dysfunction such as strain analysis assessment by two‐dimensional speckle tracking may identify patients with diastolic dysfunction before the development of LVH …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Tang and colleagues reported that plasma hs‐CRP levels progressively increase with worsening LV diastolic dysfunction. More advanced indices of LV diastolic dysfunction such as strain analysis assessment by two‐dimensional speckle tracking may identify patients with diastolic dysfunction before the development of LVH …”
Section: Discussionmentioning
confidence: 99%
“…More advanced indices of LV diastolic dysfunction such as strain analysis assessment by twodimensional speckle tracking may identify patients with diastolic dysfunction before the development of LVH. 33…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of global Lv deformation, 56,57 prediction of LV filling pressure degree, 58 diagnosis and monitoring of posttransplant acute rejection, 59,60 and prediction of cardiovascular events 61 Dyssynchrony improvement in CRT candidate selection 81 and prediction of response to CRT 79,80 controlled hypertension, but were comparable among the normal group and well-controlled hypertensive patients. Accordingly, LV torsion and twist rate had analogous trends.…”
Section: Heart Failurementioning
confidence: 99%
“…Numerous studies have shown that 3D‐STE has superior accuracy and reproducible over 2D‐STE when applied to regional myocardial strain measurements . Recent studies have demonstrated that strain assessed by 3D‐STE can predict the prognosis of patients who have suffered acute myocardial infarction and heart failure . However, different vendors’ ultrasound systems need its own analysis packages to obtain the strain values from 3D‐STE …”
Section: Introductionmentioning
confidence: 99%
“…longitudinal strain values, three-dimensional speckle-tracking echocardiography of patients who have suffered acute myocardial infarction and heart failure. 6,7 However, different vendors' ultrasound systems need its own analysis packages to obtain the strain values from 3D-STE. 1,8,9 It is inconvenient for physicians to compare strain values derived from different ultrasound systems in the same patient at different stages of a disease.…”
Section: Introductionmentioning
confidence: 99%